PEMETAAN PERSEBARAN KASUS DEMAM BERDARAH DENGUE DI DESA WEDARIJAKSA, KECAMATAN WEDARIJAKSA, KABUPATEN PATI - Adji Bayu Massaid; Retno Hestiningsih; M. Arie Wuryanto; Dwi Sutiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
DHF is a contagious disease that has become a priority public health problem in Indonesia. DHF is transmitted through female Aedes spp. Carrying the dengue virus in her body. There were 107 cases and one death in Pati Regency, the purpose of this study was to map the distribution of dengue cases and conduct a survey of Aedes spp larvae and determine the type of Aedes spp mosquito vector in the area of dengue cases that died in Wedarijaksa District. This study used a descriptive observational method with a cross sectional research design and was carried out in August - November 2020. The samples of this study were all dengue fever incidence houses in Wedarijaksa Village and houses potentially affected by dengue. From the results obtained, cases have a group pattern and the average larvae are found in the bathtub in the residents' houses. The risk of transmission in Wedarijaksa Village is classified as moderate because DF> 1 (DF = 3,3), HI> 1, BI <50%. All of the mosquito larvae found were Aedes aegypti.